2009
DOI: 10.4085/1947-380x-4.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Instructor Characteristics, Behaviors and Skills in Allied Health Care Settings: A Literature Review

Abstract: The purpose of this literature review is to compare both clinical instructor and student perceptions of helpful and hindering clinical instructor characteristics, behaviors and skills in athletic training and allied health care settings. Clinical education in athletic training is similar to that of other allied health care professions. Clinical education is used to practice didactic information in a hands-on environment, with the goal of integrating theory and practice in a controlled setting. Students are tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Poor interactions between students and preceptors hinder education. 17 Therefore, we speculate that preceptors who are not invested in their students' education are not well suited to serve as preceptors. It then falls to the clinical education coordinator to carefully select clinical sites and match students and preceptors thoughtfully.…”
Section: Role Strainmentioning
confidence: 94%
“…Poor interactions between students and preceptors hinder education. 17 Therefore, we speculate that preceptors who are not invested in their students' education are not well suited to serve as preceptors. It then falls to the clinical education coordinator to carefully select clinical sites and match students and preceptors thoughtfully.…”
Section: Role Strainmentioning
confidence: 94%
“…Developing a close and caring bond between preceptor and preceptee was found to be vital among general nursing preceptees (Gray & Smith, 2000;Lee, 1996;Neary, 1997); however, no studies on this relationship were found regarding midwifery preceptees and their preceptors. Strong interpersonal skills are necessary (Levy et al, 2009). A synthesis of qualities in preceptee-preceptor relationships suggests that preceptees valued the following in the preceptor: confidence, realistic expectations, honesty, accessibility, openness and availability (Bergman & Gaitskill, 1990;Madhavanprabhakaran et al, 2013).…”
Section: Quality #1 -Relationship With the Precepteementioning
confidence: 99%
“…One study noted that in Middle Eastern countries, preceptees believed that the preceptor's clinical competence was the most important characteristic (Madhavanprabhakaran et al, 2013). Other qualities of professional competence are commitment to the preceptee and integration of theory into practice (Bergman & Gaitskill, 1990), interest in the preceptees (Levy et al, 2009), good communication skills with regular feedback (Gray & Smith, 2000;Letizia & Jennrich, 1998;Madhavanprabhakaran et al, 2013;Myrick, 2002;Myrick & Barrett, 1994;Myrick & Young, 2001), and inspiration of the preceptee to practice confidently in the clinical environment (Happell, 2009).…”
Section: Quality #2 -Professional Competencementioning
confidence: 99%
“…Hal ini mempengaruhi proses pembelajaran klinik, sehingga menjadi kurang optimal sehingga berdampak pada pencapaian kompetensi mahasiswa. [7][8][9][10][11][12][13][14] Saat ini penanggung jawab kegiatan praktik klinik kebidanan di institusi pendidikan bidan adalah seorang koordinator. Sistem koordinator pada praktik klinik kebidanan yang selama ini berjalan terbukti belum mampu meningkatkan keterampilan klinik mahasiswa.…”
Section: Pendahuluanunclassified